2020
DOI: 10.21043/ziswaf.v7i1.7457
|View full text |Cite
|
Sign up to set email alerts
|

Peta Distribusi Zakat, Infak, Dan Sedekah (Studi Developmental pada BAZNAS Kabupaten Jombang)

Abstract: <p><em>This study describes the maps and strategies of developing the distribution of zakat, infak, and alms (ZIA) in Jombang regency. To achieve this goal, the study used field qualitative and developmental approaches, and descriptive analysis technique. </em><em>T</em><em>he zakat mustahik and the distribution target of infak and alms in Jombang are 71,421 pre prosperous families.  supporting factors: (1) the normative basis of the Qur’an and the Hadith; (2) juridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Wiradifa & Saharuddin (2018) found zakat distribution in BAZNAS South Tangerang City in three forms: traditional consumptive, traditional productive, and creative productive. Hidayati et al (2020) analysed the strategies of zakat distribution in Jombang in a productive way under the name of "Jombang Makmur," covering skills training for SMEs, working tools assistance to start/develop a business, direct capital grants, revolving capital assistance to MSMEs, and shariah business financing in the form of capital loans to SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Wiradifa & Saharuddin (2018) found zakat distribution in BAZNAS South Tangerang City in three forms: traditional consumptive, traditional productive, and creative productive. Hidayati et al (2020) analysed the strategies of zakat distribution in Jombang in a productive way under the name of "Jombang Makmur," covering skills training for SMEs, working tools assistance to start/develop a business, direct capital grants, revolving capital assistance to MSMEs, and shariah business financing in the form of capital loans to SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from direct giving by the infaq fund manager (Uyun 2015) and also using the principle of 'from the citizens, by the citizens, and for the citizens' as the embodiment of the typical Indonesian 'gotong-royong' icon (Adinugraha 2017). In addition, Hidayati, in her study, mentions that there are two approaches in the distribution of infaq funds, namely partial and structural approaches (Hidayati et al 2020). The partisan course is aimed at the poor and weak, carried out incidentally.…”
Section: Infaq As An Instrument Of Islamic Philanthropymentioning
confidence: 99%
“…Studies related to the NZI indicators have been conducted in various locations in Indonesia such as Jombang Regency (Hidayati, Chamim, Huda, & Haryanti, 2020), Kotabaru Regency (Muhamad, Aditiya, & Hafidhuddin, 2019), East Lampung Regency (Hilmiyah, Beik, & Tsabita, 2018), South Jakarta (Shalehanti, 2017), Bandung City (Farchatunnisa, 2017), Bogor (Puskas BAZNAS, 2016), Jambi (Retnowati, 2018), Bedono Village (Farikhatusholikhah & Novianti, 2018), Demak Regency (Farikhatusholikhah & Novianti, 2018), Medan City (Fahmi, 2019). They were studies that combined two provinces, such as DKI Jakarta and Bogor (Beik & Arsyianti, 2015) and several provinces in Indonesia (Puskas BAZNAS, 2016).…”
Section: Past Literature On Components Of the National Zakat Index (Nzi)mentioning
confidence: 99%
“…Furthermore, a study only focused on macro dimensions and found that the institutions involved in the studies performed in the excellent category (Pratomo & Afkar, 2020). Also, some studies focus only on micro dimensions such as distribution (Hidayati et al, 2020), collection, promotion, and socialising programs (Azis & Sukma, 2016).…”
Section: Past Literature On Components Of the National Zakat Index (Nzi)mentioning
confidence: 99%